2008
DOI: 10.1103/physrevb.77.134438
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior of CoO and NiO from specific heat, thermal conductivity, and thermal diffusivity measurements

Abstract: An ac photopyroelectric calorimeter has been used to simultaneously measure the specific heat ͑c p ͒, thermal conductivity ͑K͒, and thermal diffusivity ͑D͒ around the antiferromagnetic to paramagnetic phase transition in CoO and NiO single crystals. Up to now, no agreement on the critical behavior of both oxides has been obtained. The results for seven samples grown in different laboratories have been compared. We have found that, irrespective of the origin of the samples, the critical exponent and amplitude r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…The magnetic transition is signaled as a strong dip, whose sharpness depends on the presence of one or other rare earth ion. This kind of dips is customarily found in magnetic transitions [30][31][32][33]. Again, we have carefully checked the character of the transitions using low temperature rates, finding a complete superposition of the curves in heating and cooling runs, confirming that they are all continuous.…”
Section: Resultssupporting
confidence: 62%
“…The magnetic transition is signaled as a strong dip, whose sharpness depends on the presence of one or other rare earth ion. This kind of dips is customarily found in magnetic transitions [30][31][32][33]. Again, we have carefully checked the character of the transitions using low temperature rates, finding a complete superposition of the curves in heating and cooling runs, confirming that they are all continuous.…”
Section: Resultssupporting
confidence: 62%
“…The antiferromagnetic transition is manifested as a structure superimposed on the thermal diffusivity curve. These structures, when associated with second order phase transitions, are observed as clear dips on the monotonous decaying thermal diffusivity curve at moderately low or medium temperatures (60-600 K) [15,20,21,23,[28][29][30]. When the critical temperatures are very low and there is a quick increase of thermal diffusivity as temperature is reduced, the shape of the dip is not so marked, as it happens here; it is worth noting that the Néel temperature corresponds to the minimum value of the dip.…”
Section: Experimental Techniques and Resultsmentioning
confidence: 96%
“…The usefulness of this technique has been well demonstrated in the study of the critical behavior of second-order magnetic transitions in different materials, using the specific heat as well as the thermal diffusivity [20][21][22][23][24]. It is also an interesting technique to remove the ambiguity about the character of a phase transition, so it will also be applied in the present work to the study of the concomitant structural-magnetic phase transition that occurs near 190 K.…”
Section: Introductionmentioning
confidence: 94%
“…The BPPE was recently used once again for renewed high temperature resolution studies of the critical behaviour of the thermal parameters over the same transition in several other compounds such as KMnF3, NiO, and CoO. [76][77][78] It was shown that KMnF3 and NiO presented a Heisenberg like singularity in c, and also a cusp-like critical behaviour in the thermal resistance 1/k, similar to that obtained in RbMnF. In CoO, an anomalously large critical exponent was found for c, not consistent with any universal critical behaviour.…”
Section: Results In Solidsmentioning
confidence: 99%